A comparative study to assess the knowledge of people regarding dengue fever, its causes, sign and symptoms, treatment, prevention and control in rural and urban communities in selected areas of district Faridkot, Punjab - Kaur, Mandeep; Kaur, Pabal Preet (International Journal Of Community Medicine And Public Health, 2025)
Background: Dengue is a vector-borne disease that possess a major public health threat globally. It is a viral disease caused by the infection of dengue virus, a Flavivirus, spreads through bite of infected female Aedes aegypti and Aedes albopictus mosquitoes. The present study was undertaken to find out the knowledge among the general population of Faridkot. Methods: Comparative research study conducted in Puri colony of urban area and Village Kamiana of rural area of district Faridkot. Data was collected from 100 sample between age of 15 to 60 years from selected urban and rural community by using non probability convenient sampling. The collected data were group and analysed by descriptive and inferential statistics. Results: Results of the study revealed that in rural community most of the samples (82%) has inadequate knowledge regarding dengue fever whereas only 18% has adequate knowledge. In urban community, more than half (58%) has inadequate knowledge whereas 42% has adequate knowledge dengue fever. Level of knowledge was found to be significant with age, gender, education, occupation, source of water. Conclusions: As in both the communities more than half of the sample had inadequate knowledge regarding dengue fever. So, it was concluded that there is need to improve the knowledge of people regarding dengue fever in urban and rural community.